Directional spiral stent with functions of promoting tendon formation and inhibiting ossification as well as preparation method and application of directional spiral stent
The ZIF-8@RAPA functional bionic scaffold constructed using electrospinning technology in tendon injury repair solves the problem of difficult inhibition of ectopic ossification in the prior art, and achieves effective tendon repair and mechanical performance improvement.
Patent Information
- Application Number
- CN202411538395.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The prior art is difficult to effectively inhibit ectopic ossification in the treatment of tendon injuries, resulting in a gap in the quality of repair and natural tendon ECM.
Using electrospinning technology, ZIF-8@RAPA and PCL/COLⅠcopy directional microcurl nanofibers are cospinated to construct a functional bionic scaffold that can specifically deliver RAPA to pathological tendons, which is used to repair damaged Achilles tendons and inhibit ectopic bones. change.
This directional spiral stent can effectively repair the damaged Achilles tendon, while inhibiting the occurrence of ectopic ossification during the Achilles tendon repair, with excellent mechanical properties and good long-term drug sustained release effect.
Smart Images

Figure CN119405883A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedicine, and in particular relates to a directional spiral stent with the functions of promoting tendonization and inhibiting ossification, and a preparation method and application thereof. Background Art
[0002] Tendon injury refers to the injury caused by rapid contraction or excessive stretching of the tendon during exercise, accounting for about 30% of musculoskeletal system diseases. Since tendons have the characteristics of few cells, few blood vessels and low metabolism, their endogenous repair ability is poor. At present, the methods for treating tendon injuries mainly include surgical suturing, autologous (allogeneic / xenogeneic) transplantation, etc. However, in clinical applications, these methods are often limited by problems such as insufficient repair, limited sources, donor site complications, and immune rejection. Therefore, it is necessary to find new methods to overcome the defects of existing treatment methods and achieve the treatment of tendon injuries.
[0003] Scaffolds are a biomimetic extracellular matrix (ECM) that can provide structural support for stem cells and form a physicochemical microenvironment that can regulate the fate of stem cells. With the development of tissue engineering technology, many researchers have tried to construct tissue engineering tendons by simulating the composition, topological structure, and mechanical properties of natural tendon ECM, providing a biomimetic microenvironment for the directional differentiation of stem cells into the tendon system, thereby accelerating the endogenous healing process of tendons. Existing studies have shown that tendon ECM is mainly composed of micro-curled parallel collagen fibers; parallel nanofibers promote the differentiation of stem cells into the tendon lineage, while randomly arranged nanofibers promote the differentiation of stem cells into the bone system. On the one hand, spiral scaffolds can reduce the local maximum strain of cells during stretching, maintain high vitality, and promote the dynamic repair of tendon tissue; that is, directional spiral scaffolds can induce the differentiation of tendon stem cells (TSCs) into the tendon system. On the other hand, scaffold materials can also be used as an effective delivery system for drug release at the site of tissue injury, and their chemical microenvironment can induce the differentiation behavior of stem cells. A large number of studies have shown that the histological characteristics of heterotopic ossification (HO) are common in the late stage of tendon repair, resulting in a certain gap between its mechanical properties and repair quality and those of natural tendon ECM. Therefore, in tendon injury repair, timely and appropriate inhibition of TSCs bone differentiation can avoid the occurrence of HO. Therefore, the directional helical scaffold that can be used as a drug delivery carrier is an ideal tissue engineering scaffold for bionic tendon ECM.
[0004] In the prior art, the CN112023060B patent discloses a dual-drug loaded nano-microsphere targeting cartilage with photothermal response characteristics. It uses small-particle mesoporous polydopamine as the matrix, and reacts with FeCl3·6H2O and H3BTC in sequence to form a metal organic framework on the surface of mesoporous polydopamine. The obtained MPDA-MOF nano-microspheres are then reacted with EDC and NHS solutions to activate the carboxyl groups on the surface of MOF, and are connected with the amino groups in the type II collagen targeting peptide to form composite nano-microspheres with surface-loaded cartilage targeting peptides. The bilirubin and rapamycin dual factors are correspondingly loaded in the MOF shell and the pores of mesoporous polydopamine, and finally RB@MPMW is obtained. The invention uses mesoporous polydopamine to load bilirubin and rapamycin for targeted treatment of cartilage degeneration in osteoarthritis. Summary of the invention
[0005] In view of this, in order to solve the problem of heterotopic ossification in tendon injury repair, the present invention proposes a directional spiral stent that promotes tendon healing and inhibits heterotopic ossification, as well as its preparation method and application. The present invention takes the synergistic effect of inhibiting osteogenesis and promoting bonding as the starting point, and uses electrospinning technology to co-spin ZIF-8@RAPA and PCL / COLⅠ directional micro-curled nanofibers to construct a functional bionic stent that can specifically deliver RAPA to pathological tendons. The stent can effectively repair damaged Achilles tendons and inhibit the occurrence of heterotopic ossification during the Achilles tendon repair process.
[0006] One of the objectives of the present invention is to provide a composition for preparing a directional helical stent.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] A composition for preparing an oriented helical stent, the composition comprising a composition A for preparing an outer layer of a nanofiber membrane and a composition B for preparing an inner layer of a nanofiber membrane;
[0009] The composition A comprises the following components: polycaprolactone and type I collagen at a concentration of 10% to 20%; in the composition A, the mass ratio of type I collagen to polycaprolactone is 15 to 25:100;
[0010] The composition B comprises the following components: polycaprolactone with a concentration of 10% to 20% and a drug; in the composition B, the mass ratio of the drug to the polycaprolactone is 5 to 10:100; the drug is rapamycin with ZIF-8 as a carrier;
[0011] The nanofiber membrane is made into a directional spiral stent by mechanical rotation.
[0012] Preferably, the composition A comprises polycaprolactone and type I collagen at a concentration of 15%; in the composition A, the mass ratio of type I collagen to polycaprolactone is 20:100.
[0013] Preferably, the composition B comprises polycaprolactone at a concentration of 15% and a drug; in the composition B, the mass ratio of the drug to the polycaprolactone is 7:100.
[0014] Most preferably, the drug is ZIF-8@RAPA.
[0015] Furthermore, the composition A also contains hexafluoroisopropanol; the composition B also contains dichloromethane and DMF, and the volume ratio of the dichloromethane to DMF is 2 to 5:1.
[0016] Preferably, the volume ratio of dichloromethane to DMF is 3:1.
[0017] Furthermore, the nanofiber membrane is a sandwich structure.
[0018] A second object of the present invention is to provide a method for preparing a directional helical stent using the above composition.
[0019] To achieve the above object, the present invention adopts the following technical solutions:
[0020] The method for preparing a directional helical stent using the above composition comprises the following steps:
[0021] (1) Using ZIF-8 as a delivery vector for rapamycin to prepare ZIF-8@RAPA;
[0022] (2) The outer layer uses hexafluoroisopropanol as solvent, polycaprolactone and type I collagen as solutes; the inner layer uses a mixed solution of dichloromethane and DMF as solvent, polycaprolactone and ZIF-8@RAPA obtained in step (1) as solutes; and a nanofiber membrane is prepared by electrospinning technology;
[0023] (3) The nanofiber membrane obtained in step (2) is mechanically stirred to prepare a directional spiral stent.
[0024] Furthermore, the particle size of the ZIF-8@RAPA is 190nm to 300nm.
[0025] Further, step (1) specifically includes the following steps:
[0026] 1) dissolving zinc nitrate hexahydrate, and adding RAPA methanol solution to prepare a zinc-based solution;
[0027] 2) using 2-methylimidazole as solute and methanol as solvent to prepare an imidazole solution;
[0028] 3) adding the zinc-based solution obtained in step 1) to the imidazole solution obtained in step 2) to react and obtain ZIF-8@RAPA.
[0029] Preferably, the solvent of the zinc nitrate hexahydrate is methanol.
[0030] Preferably, in step 1), the final concentration of the RAPA methanol solution is 730 μg / mL.
[0031] Preferably, in step 3), the reaction conditions are as follows: stirring for 3 to 10 minutes, standing for 50 to 57 minutes, and the total reaction time is 60 minutes.
[0032] As the most preferred embodiment, in step 3), the reaction conditions are: stirring for 5 minutes and standing for 55 minutes.
[0033] Preferably, the final concentration of zinc ions is 0.015 to 0.025 mol / L; 2-mIm - The final concentration is 0.10-0.2 mol / L; the concentration ratio of the zinc nitrate hexahydrate to the 2-methylimidazole is 1:7-10.
[0034] As the most preferred, the final concentration of zinc ion is 0.0175 mol / L; 2-mIm - The final concentration is 0.14 mol / L; the concentration ratio of the zinc nitrate hexahydrate to the 2-methylimidazole is 1:8.
[0035] Further, after the reaction in step 3) is completed, the resulting solution is centrifuged, washed, and dried to obtain ZIF-8@RAPA;
[0036] Preferably, the centrifugal speed is 8000 rpm and the time is 10 min;
[0037] Preferably, the washing is performed three times with methanol.
[0038] Preferably, the drying is carried out in a vacuum drying oven at 25°C for 24 hours.
[0039] Furthermore, in step (2), the preparation parameters of electrospinning are: shaft speed 3500-4500 rpm, voltage 20-30 kV, injection speed 0.4-0.7 mL / h, and receiving distance 15-20 cm.
[0040] Preferably, the preparation parameters of the electrospinning are: shaft speed 4000 rpm, voltage 25 kV, injection speed 0.5 mL / h, and receiving distance 18 cm.
[0041] Furthermore, the nanofiber membrane obtained in step (2) has a sandwich structure.
[0042] Furthermore, step (3) specifically includes: cutting the nanofiber membrane into 12 mm×80 mm, fixing it on an improved mechanical stirring shaft for rotation treatment, setting the rotation speed to 30 rpm, and preparing the directional spiral stent.
[0043] The third object of the present invention is to provide a directional spiral stent prepared by the above-mentioned preparation method.
[0044] Furthermore, the number of spiral turns of the directional spiral stent is evenly distributed, and the width of a single turn is about 500 μm.
[0045] Furthermore, the fibers in the oriented spiral stent exhibit obvious orientation distribution, and there is a porous structure between the fibers.
[0046] A fourth object of the present invention is to provide a nano preparation for treating and repairing tendon injuries and / or inhibiting the occurrence of heterotopic ossification.
[0047] To achieve the above object, the present invention adopts the following technical solutions:
[0048] A nano preparation for treating and repairing tendon injuries and / or inhibiting heterotopic ossification, the nano preparation consists of a drug and a carrier; the drug is RAPA; the carrier is ZIF-8; the nano preparation is prepared by a pharmaceutically acceptable method.
[0049] A fifth object of the present invention is to provide a use of the aforementioned composition, the aforementioned directional helical stent and / or the aforementioned nano-preparation in the preparation of a product for repairing tendon damage and / or inhibiting the occurrence of heterotopic ossification.
[0050] The beneficial effects of the present invention are:
[0051] 1. The present invention takes the synergistic effect of inhibiting osteogenesis and promoting bonding as the starting point, and uses electrospinning technology to co-spin ZIF-8@RAPA and PCL / COLⅠ to oriented micro-curled nanofibers to construct a functional bionic scaffold that can specifically deliver RAPA to pathological tendons. This oriented spiral scaffold can effectively repair damaged Achilles tendons and inhibit the occurrence of heterotopic ossification during Achilles tendon repair, and has broad application prospects.
[0052] 2. The oriented helical stent (aNFs / Z@R helical stent) of the present invention has a uniform distribution of helical turns, the fibers in the stent show obvious orientation distribution, and there is a porous structure between the fibers, which is conducive to cell migration.
[0053] 3. The directional spiral stent of the present invention has an elastic modulus of about 20.64±2.25 MPa and a breaking strength of about 51.92±9.02 MPa, and has excellent mechanical properties.
[0054] 4. The present invention found that the oriented helical scaffold (aNFs / Z@R(helical)) of the present invention is superior to aNFs(helical) without ZIF-8@RAPA in terms of mechanical properties and inhibition of heterotopic ossification. It is confirmed that the fiber topology of the oriented helical scaffold and ZIF-8@RAPA can inhibit the occurrence of heterotopic ossification to a certain extent, and the two play a synergistic role.
[0055] 5. The present invention uses ZIF-8 as a delivery carrier of rapamycin. The constructed directional spiral stent containing ZIF-8@RAPA has good long-term sustained drug release effect, pH sensitivity and cell compatibility. It can continuously release RAPA in the inflammatory environment in the body and inhibit the formation of heterotopic ossification. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is the result diagram of ZIF-8 characterization, where: Figure 1 -A is the pH monitoring graph of Z1-Z4; Figure 1 -B is the pH monitoring graph of Z5-Z8; Figure 1 -C is the test result diagram of the effect of different stirring times on particle size; Figure 1 -D is the particle size distribution diagram of Z1-Z4; Figure 1 -E is the particle size distribution diagram of Z5-Z8; Figure 1 -F is the XRD pattern of Z1-Z8;
[0057] Figure 2 The morphology and particle size characterization results of ZIF-8@RAPA and ZIF-8 are shown in Figure 1. Figure 2 -A is the SEM image of ZIF-8; Figure 2 -B is the SEM image of ZIF-8@RAPA; Figure 2 -C is the particle size distribution diagram of ZIF-8 and ZIF-8@RAPA;
[0058] Figure 2 -D is the TEM image of ZIF-8; Figure 2 -E is the TEM image of ZIF-8@RAPA; Figure 2 -F is the statistical diagram of the average particle size of ZIF-8 and ZIF-8@RAPA;
[0059] Figure 3 The results of characterization of the structure and physicochemical properties of ZIF-8@RAPA and ZIF-8 are shown in Figure 2. Figure 3 -A is the XRD pattern of ZIF-8@RAPA and ZIF-8; Figure 3 -B is the FTIR images of ZIF-8@RAPA and ZIF-8; Figure 3 -C is the UV-vis image of ZIF-8@RAPA and ZIF-8; Figure 3-D is the TGA graph of ZIF-8@RAPA and ZIF-8; Figure 3 -E is the Zeta potential diagram of ZIF-8@RAPA and ZIF-8; Figure 3 -F is a graph of the cumulative release rate of RAPA under different pH conditions of ZIF-8@RAPA;
[0060] Figure 4 It is a statistical chart of drug loading rate at different RAPA addition amounts;
[0061] Figure 5 The characterization results of the morphology, fiber orientation and fiber diameter of aNFs / Z@R and rNFs / Z@R are shown in Figure 2. Figure 5 -A is the SEM image of aNFs / Z@R; Figure 5 -B is the fiber direction distribution statistics of aNFs / Z@R; Figure 5 -C is the fiber diameter distribution statistics of aNFs / Z@R; Figure 5 -D is the SEM image of rNFs / Z@R; Figure 5 -E is the fiber direction distribution statistics of rNFs / Z@R; Figure 5 -F is the statistical diagram of fiber diameter distribution of rNFs / Z@R;
[0062] Figure 6 TEM image of ZIF-8@RAPA in a single fiber;
[0063] Figure 7 The stress-strain curves of aNFs / Z@R and rNFs / Z@R nanofiber membranes;
[0064] Figure 8 The graph shows the test results of drug sustained release behavior of aNFs / Z@R nanofiber membrane in PBS (pH 6.5 and pH 7.2) within 14 days;
[0065] Fig. 9 The figure shows the cell compatibility test results of aNFs / Z@R nanofiber membrane, where: Fig. 9 -A is the SEM image of aNFs / Z@R nanofiber membrane; Fig. 9 -B is the Live / Dead staining image of aNFs / Z@R nanofiber membrane; Fig. 9 -C is the EdU staining image of aNFs / Z@R nanofiber membrane;
[0066] Fig.10 The macroscopic morphology of aNFs / Z@R helical scaffold;
[0067] Fig.11 This is a microscopic magnified image of the aNFs / Z@R helical scaffold;
[0068] Fig.12 The macroscopic morphology of rNFs / Z@R helical scaffold;
[0069] Fig.13 This is a microscopic magnified image of the rNFs / Z@R helical scaffold;
[0070] Fig.14 Diagram of the surgical procedure for the Achilles tendon defect model established in SD rats;
[0071] Fig.15 The following are representative micro-CT three-dimensional reconstruction images of the Achilles tendon in each group 6 weeks after surgery. Fig.15 -A is a representative micro-CT three-dimensional reconstruction of the Achilles tendon in the aNFs / Z@R (spiral) group 6 weeks later; Fig.15 -B is a representative micro-CT three-dimensional reconstruction of the Achilles tendon in the aNFs (spiral) group 6 weeks later; Fig.15 -C is a representative micro-CT three-dimensional reconstruction of the Achilles tendon in the rNFs / Z@R(helical) group 6 weeks later;
[0072] Fig.16 The following are representative HE staining images of the Achilles tendons of each group 6 weeks after surgery. Fig.16 -A is a representative HE staining image of the Achilles tendon in the aNFs / Z@R (spiral) group 6 weeks after surgery; Fig.16 -B is a representative HE staining image of the Achilles tendon in the aNFs (spiral) group 6 weeks after surgery;
[0073] Fig.16 -C is a representative HE staining image of the Achilles tendon in the rNFs / Z@R(helical) group 6 weeks after surgery. DETAILED DESCRIPTION
[0074] The technical solution of the present invention will be further described clearly and completely in conjunction with specific embodiments below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present invention.
[0075] At present, the pathogenesis of HO in tendon tissue is still unclear, but it may be related to the mTOR signaling pathway. Existing studies have found that mTOR inhibition can slow down tendon ossification after Achilles tendon amputation in rats. Rapamycin (RAPA) is an inhibitor of the mTOR signaling pathway, and its target can regulate HO in multiple tissues. Therefore, RAPA can prevent tendon HO by regulating the abnormal differentiation of TSCs. However, the in vivo bioavailability of RAPA is very low, which can easily cause the problem of failure before reaching the diseased site. Metal-organic framework (MOF) materials represented by zeolitic imidazolate framework (Zeolitic Imidazolate Framework-8, ZIF-8) show excellent drug delivery capabilities in terms of drug sustained release and pH-responsive release. ZIF-8 is formed by self-assembly of zinc ions and 2-methylimidazole. Its crystallization process is similar to that of zeolite, and stable ZIF-8 crystals are formed after stages such as nucleation and crystal growth. Since ZIF-8 has the advantages of high surface area, high porosity, adjustable pore size and shape, stable physical and chemical properties, etc., and there are active binding sites in the framework, which can adsorb various molecules (genes, drugs, peptides, nucleic acids, proteins, etc.), it can be used as a carrier of drug delivery system to achieve the sustained release function of loaded drugs. Therefore, in view of the problem of heterotopic ossification in tendon injury repair, the present invention takes the synergistic effect of inhibiting osteogenesis and promoting bonding as the entry point, uses ZIF-8 as a RAPA delivery carrier (ZIF-8@RAPA), and uses electrospinning technology to co-spin ZIF-8@RAPA with PCL / COLⅠ to form oriented micro-curled nanofibers, and constructs a functionalized bionic scaffold that can specifically deliver RAPA to pathological tendons for the repair of damaged Achilles tendons.
[0076] In the present invention, it is considered that particle size is an important parameter of drug delivery carrier, which determines its biodistribution, cell internalization, tissue clearance and metabolism in vivo, which play a vital role in the therapeutic effect. Studies have shown that micrometer-scale ZIF-8 usually does not enter the interior of the cell, has poor biocompatibility, and may cause a certain immune response. And nanometer-scale ZIF-8 can pass through the cell membrane to achieve effective distribution of drugs in vivo, and has good biocompatibility and low toxicity. Specifically, the nanocarrier size should not exceed 200nm, and particles of 20-30nm will be absorbed and eliminated by the kidney system, while particles of 30-300nm are absorbed by mononuclear phagocytes and subsequently stored in organs such as the liver, spleen or bone marrow. Accordingly, the present invention selects to encapsulate RAPA using 100-200nm ZIF-8, and uses directional spiral stent as a delivery system to enable RAPA to achieve the regulation of TSCs differentiation at the tendon injury site by local sustained release. In the present invention, the particle size of ZIF-8 is controlled to be 100-200 nm by optimizing the synthesis conditions, such as reaction time, stirring time, standing time, etc.
[0077] In the examples of the present invention, basic information of key reagents / materials involved is shown in Table 1.
[0078] Table 1. Basic information of key reagents / materials
[0079] Reagents / Materials factory effect <![CDATA[Zinc nitrate hexahydrate (Zn(NO3)2·6H2O, 99%)]]> Chengdu Kelong Chemicals Co., Ltd. Preparation of ZIF-8 drug carrier <![CDATA[2-Methylimidazole (C4H6N2, 98%)]]> MACKLIN Preparation of ZIF-8 drug carrier Rapamycin (98%) Aladdin Drugs to repair tendon damage Methanol (99.5%) Aladdin Reaction solvent Polycaprolactone (PCL) SIGMA-ALDRICH Construction of nanofiber scaffolds Collagen type I (COLI) MACKLIN Construction of nanofiber scaffolds Hexafluoroisopropanol Aladdin Dissolve PCL and collagen Dichloromethane Chongqing Chuandong Chemical Dissolving PCL Dimethylformamide (DMF) Chongqing Chuandong Chemical Dissolving PCL Phosphate buffered saline (PBS) Anhui Biosharp Simulated body fluid
[0080] In the embodiment of the present invention, the basic information of the key instruments involved is shown in Table 2.
[0081] Table 2. Basic information of key instruments
[0082] equipment factory effect Centrifuge Xiangyi Centrifugation of ZIF-8 Electrospinning Machine Qingdao Pansi Technology Preparation of nanofiber scaffolds Electronic balance ThermoFisherScientific Weighing Ultrapure water system ThermoFisherScientific Purified water Field Emission Scanning Electron Microscope JEOL Morphology observation Transmission electron microscopy FEITecnaiG212 Morphology observation ELISA reader ThermoFisherScientific Absorbance measurement Universal Mechanical Stretching Machine Zhuhai Sansi Taijie Fiber membrane mechanical properties test
[0083] In the present invention, the preparation method of the bionic spiral scaffold (aNFs / Z@R spiral scaffold) comprises the following steps:
[0084] (1) Preparation of ZIF-8@RAPA: Dissolve 0.3 g of zinc nitrate hexahydrate in 14.3 mL of methanol, add 3.5 mL of 6 mg / mL RAPA methanol solution (final concentration 730 μg / mL), stir for 5 min, and obtain a zinc-based solution (zinc ion concentration 0.0175 mol / L). Dissolve 0.66 g of 2-methylimidazole solution in 14.3 mL of methanol to obtain an imidazole solution (2-methylimidazole solution). - The zinc-based solution was added to the imidazole solution, stirred for 5 min, and allowed to stand for 55 min; centrifuged at 8000 rpm for 10 min, washed with methanol three times, and then dried in a vacuum oven at 25°C for 24 h to obtain ZIF-8@RAPA.
[0085] (2) Preparation of nanofiber membrane (NFs / Z@R)
[0086] The outer layer uses hexafluoroisopropanol as solvent, polycaprolactone with a concentration of 15% (w / v) and type I collagen with a concentration of 18.75% (w / w, accounting for the mass ratio of polycaprolactone) as solute, and the inner layer uses dichloromethane:DMF=3:1 as solvent, PCL with a concentration of 15% (w / v) and ZIF-8@RAPA with a concentration of 7% (w / w, accounting for the mass ratio of polycaprolactone) as solute. The nanofiber membrane with a "sandwich structure" was prepared by electrospinning technology; the preparation parameters of the highly oriented spinning membrane were: shaft speed 4000rpm, voltage 25kV, injection speed 0.5mL / h, receiving distance 18cm; a nanofiber membrane with a "sandwich structure" was obtained.
[0087] (3) Preparation of directional helical stents
[0088] The sandwich-structured nanofiber membrane was cut into 12 mm × 80 mm pieces, fixed on an improved mechanical stirring shaft, and the rotation speed was set to 30 rpm to prepare the NFs / Z@R spiral scaffold.
[0089] Example 1. Synthesis and characterization of ZIF-8
[0090] (1) Synthesis of ZIF-8
[0091] Dissolve zinc nitrate hexahydrate in 14.3 mL of methanol and ultrasonically dissolve for 10 minutes to obtain a zinc nitrate solution. Dissolve 2-methylimidazole in 14.3 mL of methanol and ultrasonically dissolve for 10 minutes to obtain a 2-methylimidazole solution. Quickly add the zinc nitrate solution to the 2-methylimidazole solution and stir for a certain period of time to obtain a white suspension, which is ZIF-8. Collect the product by centrifugation at 8000 rpm for 10 minutes, wash it with methanol 3 times to fully remove the unreacted reactants, and then dry it at 75°C in a vacuum oven for 24 hours to collect the ZIF-8 particles.
[0092] (2) Characterization of ZIF-8
[0093] Further investigate the effect of synthesis conditions on ZIF-8 particle size and yield. Because the pH of the reaction system changes with the change of synthesis time, the change of pH value reflects the evolution of ZIF-8 crystalline structure to a certain extent. Therefore, the present embodiment first monitors pH to 8 groups of solutions with different raw material ratios and different concentrations. Secondly, stirring time is a key parameter in the ZIF-8 synthesis process, which affects the mixing degree, nucleation process and crystal growth between the reactants. Insufficient stirring may cause uneven crystal nucleation, and excessive stirring may cause too much nucleus formation. Therefore, further explore the appropriate stirring time to obtain nanoparticles with small and uniform particle size distribution. Specific experimental methods and results are as follows:
[0094] 1) Grouping
[0095] The concentrations of zinc nitrate hexahydrate and 2-methylimidazole were changed, and two concentration ratios of 1:8 and 1:16 were set, with four concentration gradients totaling 8 groups, as shown in Table 3 for details.
[0096] Table 3. Initial concentration, final reactant concentration, and reactant concentration ratio for the synthesis of ZIF-8 particles
[0097]
[0098] 2) Condition optimization
[0099] The pH of the solution was monitored at intervals of 10 minutes each time until the pH was stable for 30 minutes. According to the pH monitoring results, the total reaction time was kept unchanged, and only the stirring time and the standing time were changed to explore the effect of the stirring time on the ZIF-8 particle size, as shown in Table 4. Finally, based on the stirring time results, the effect of the reactant concentration on the ZIF-8 particle size and yield was studied.
[0100] ZIF-8 particle yield = ZIF-8 actual yield / ZIF-8 theoretical yield × 100%.
[0101] Table 4. Changing stirring time under the same reactant concentration
[0102] ZIF-8 Number Mixing time (minutes) Standing time (minutes) J5 5 55 J15 15 45 J30 30 30 J60 60 0
[0103] (3) Results and discussion
[0104] The pH monitoring results of Z1-Z4 are as follows Figure 1 -A, the pH monitoring results of Z5-Z8 are as follows Figure 1 -B. In general, when zinc nitrate hexahydrate (Zn 2+ ) and 2-methylimidazole (2-mIm - ) ratio remains unchanged, with the increase of ion concentration, the initial pH and corresponding stable pH of the reaction system tend to increase. Similarly, when Zn2+ The concentration remains constant, with 2-mIm - With the increase of concentration, the initial pH and stable pH still showed an upward trend. It is worth noting that the pH of each group showed a similar trend with the synthesis time, including three obvious stages, namely S Ⅰ :When the crystallization time (t) is less than 10min, the pH drops suddenly; S Ⅱ :When 10min<t<50min, the pH drop rate slows down significantly; S Ⅲ :When t≥60min, pH is basically stable. Therefore, in order to synthesize ZIF-8 nanocarriers with small particle size and high crystallinity, the synthesis time is selected as 60min.
[0105] The test results of the effect of different stirring times on particle size are as follows: Figure 1 -C. The present invention takes Z1 as an example to explore the effect of stirring time on the particle size of ZIF-8. After the two reactants are mixed evenly, the total reaction time is kept unchanged, and the stirring time and the standing time are changed. The results show that as the stirring time increases, the particle size gradually increases. When the stirring time is increased to 60min, large particle crystals are formed, and the particle size distribution is bimodal. When stirring for 5min and standing for 55min, the minimum particle size is 163nm. Therefore, according to the above results, the reaction conditions are optimized as follows: total reaction time 60min, stirring 5min, standing for 55min.
[0106] Based on the above optimized conditions, Z1-Z8 were synthesized. Figure 1 -D and Figure 1 -E, when [Zn 2+ ] / [2-mIm - ] is unchanged, and the particle size gradually increases with the increase of ion concentration. Within a certain concentration range, when the reaction system keeps the concentration of zinc nitrate hexahydrate unchanged, increasing [2-mIm - ] can reduce the particle size of ZIF-8 (Z2-Z4 vs. Z6-Z8), which may be because the excess imidazole can provide more ligands to promote nucleation, while the number of zinc ions available for each nucleus is relatively reduced, thus forming smaller crystals. 2+ ] is 0.0175 mol / L, and its trend is just the opposite (D Avg (Z1)=163.8nm±3.1nmvs.D Avg (Z5) = 245.7 nm ± 5.5 nm). This may be because when the ion concentration is too low, the nucleation rate of ZIF-8 is low, and the increase of [2-mIm -] may increase the probability of random nucleation, thereby increasing the particle size. Further, in order to explore the effects of different concentrations and ratios on the crystal structure of ZIF-8, the present invention conducted X-ray diffraction (XRD) analysis on the solid products of Z1-Z8. The results are as follows Figure 1 -F shows that the characteristic peaks of each group are narrow and sharp and the peak positions are basically the same. The main diffraction peaks such as (011), (002), (112), (022), (013), and (222) are observed, which is consistent with the existing literature reports. This result shows that changing the concentration and ratio of the reactants within a certain range has no effect on the main lattice of ZIF-8. But at the same time, it can be observed that the peak intensity of (011) of the Z1 group is higher than the peak intensity of (112), which is consistent with the theory, while the trends of the two crystal planes of other groups are just the opposite. Literature reports that before the crystal grows to maturity, the relative crystallinity of ZIF-8 increases with the increase of synthesis time. At this stage, the most important (011) peak of ZIF-8 will increase with the extension of time and become the strongest peak. Therefore, the above phenomenon may be because Z2-Z8 is still in the middle stage of crystal growth, the (011) crystal plane has not grown fully, and the crystal has not reached maturity.
[0107] The yields of the products of each group Z1-Z8 were calculated, and the results are shown in Table 5. In general, the solid yield was higher when the reactant molar ratio was 1:8 than when it was 1:16. When the reactant molar ratio was fixed, the ZIF-8 yield decreased with the increase of ion concentration. The yield of Z1 was 51.20%, which was the highest among the 8 groups, and the yield was basically close to that reported by Beh et al.
[0108] Based on the above experimental results, the optimal synthesis condition of ZIF-8 is Z1, that is, [Zn 2+ ]=0.0175mol / L,[2-mIm - ]=0.14mol / L, stirred at room temperature for 5min, and allowed to stand for 55min. Under this condition, nano-ZIF-8 with high crystallinity, good uniformity and good dispersibility can be prepared, which is suitable as a drug delivery carrier.
[0109] Table 5. Different Zn 2+ and 2-mIm - Particle size and solid phase yield of ZIF-8 at different concentrations
[0110]
[0111]
[0112] Example 2. Preparation and characterization of ZIF-8@RAPA
[0113] The optimal synthesis conditions of ZIF-8 obtained according to Example 1 are: [Zn 2+]=0.0175mol / L,[2-mIm - ]=0.14mol / L, stirred at room temperature for 5min, and allowed to stand for 55min; further synthesized ZIF-8@RAPA nanoparticles; and used ZIF-8 as a control group to characterize the structure and physicochemical properties of ZIF-8@RAPA. The specific methods and results are as follows:
[0114] (1) Preparation method of ZIF-8@RAPA
[0115] Dissolve 0.3g zinc nitrate hexahydrate in 14.3mL methanol, add 1mL, 2mL, 3mL, 3.5mL, and 4mL of RAPA methanol solution with a concentration of 6mg / mL, respectively, and stir for 5min to obtain a zinc-based solution. Dissolve 0.66g 2-methylimidazole solution in 14.3mL methanol to obtain an imidazole solution. Add the zinc-based solution to the imidazole solution, stir for 5min, and let stand for 55min; use a centrifuge to centrifuge at 8000rpm for 10min to separate the resulting particles, and wash them three times with methanol. Dry in a vacuum oven at 25℃ for 24h to obtain ZIF-8@RAPA.
[0116] (2) Characterization of the structure and physicochemical properties of ZIF-8@RAPA
[0117] 1) Dynamic light scattering analysis (DLS): Using a Malvern ZetasizerNano ZS laser particle size analyzer, take an appropriate amount of sample, disperse it in water and dilute it to a suitable concentration, and ultrasonicate it for 15 minutes. Each ZIF-8 sample is measured at least three times to obtain the average data.
[0118] 2) Scanning electron microscopy (SEM): An appropriate amount of sample was dispersed on the conductive glue, gold was sprayed for 60 seconds, and the morphology was observed and photographed using a JSM-7800F scanning electron microscope from JEOL.
[0119] 3) X-ray diffraction (XRD): The dried nanoparticles were ground and loaded on the sample stage, and the sample and the edge of the sample stage were kept at the same level. The measurement was performed using a Rigaku SmartLab-9 X-ray diffractometer. Test conditions: scanning angle of 5°-60°, speed of 5° / min.
[0120] 4) Transmission electron microscopy (TEM): The dried ZIF-8 was dispersed in an ethanol solution and dropped onto the carbon film copper grid using a disposable dropper. After drying, its morphology was observed using a FEI Tecnai G212 transmission electron microscope.
[0121] 5) Infrared spectroscopy analysis (FTIR): 2 mg of sample was mixed with 200 mg of KBr powder, ground into powder in an agate mortar and pressed into a sheet (16 MPa, 2 min). Recorded at 4000-400 cm -1 Spectrum within the range.
[0122] 6) Thermogravimetric analysis (TG): The temperature range was 25°C to 700°C in a nitrogen atmosphere with a constant heating rate of 10°C / min.
[0123] 7) Ultraviolet absorption spectrum (UV): RAPA, ZIF-8 and ZIF@RAPA were dispersed in methanol solution respectively, and their absorption curves in the wavelength range of 200-400 nm were measured using an ultraviolet spectrophotometer.
[0124] (3) Results and analysis
[0125] SEM and TEM were used to observe the material morphology. Figure 2 -A. Figure 2 -B, the synthesized ZIF-8@RAPA has a similar morphology to ZIF-8 and a relatively uniform particle size. Figure 2 -D. Figure 2 -E, the crystals are regular hexagons, which are the projections of the {110} face in the rhombic dodecahedron, consistent with the literature reports. The particle size distribution of the two nanoparticles in aqueous solution was measured using a Malvern particle size analyzer. The results are shown in Figure 2 -C. Figure 2 -F, the measured particle size distributions of ZIF-8@RAPA and ZIF-8 are narrow (190.1nm-295.3nm vs. 122.4nm-190.2nm), and their average particle sizes are 257.4±4.6nm and 163.8±3.1nm, respectively.
[0126] XRD, FTIR, and UV-vis were used to further characterize the structures of ZIF-8@RAPA and ZIF-8. Figure 3 -A, the main peak positions of the diffraction peak spectra of ZIF-8@RAPA and ZIF-8 are basically consistent with the previously reported ZIF-8 XRD curve. At the same time, no obvious RAPA characteristic peaks appear in the XRD peak spectrum of ZIF-8@PAPA, which can be inferred that RAPA is successfully encapsulated in ZIF-8. The FTIR test results are shown in Figure 3 -B, similar to ZIF-8, ZIF-8@RAPA has a peak at 3128 cm -1 、2935cm -1 、1585cm -1The absorption peak at 420cm-1 is attributed to the stretching vibration of aromatic CH bonds, aliphatic CH bonds and CN bonds in 2-mIm; -1 The absorption peak at is the stretching vibration peak of the Zn-N bond. 2+ The coordination with 2-mIm indicates that ZIF-8@RAPA has the same complete framework structure as ZIF-8. It is worth noting that ZIF-8@RAPA has a -1 The smaller absorption peak at the corresponding carbonyl stretching vibration peak in RAPA indicates that most RAPA is successfully loaded in the ZIF-8 framework structure, and a few are adsorbed on its surface. From the UV-vis spectrum, we can see that the characteristic absorption peak of Zn in ZIF-8 is around 223nm, and the characteristic absorption peak of RAPA is 278nm. ZIF-8@RAPA has both of the above characteristic absorption peaks (225nm, 278nm), indicating that RAPA is loaded in ZIF-8 crystals. For details, see Figure 3 -C.
[0127] The thermal stability of ZIF-8@RAPA and ZIF-8 was further tested by TGA. Figure 3 -D, as the temperature rises, ZIF-8@RAPA and ZIF-8 begin to lose weight and collapse at 420°C, and complete the first weight loss at around 520°C. At this temperature, ZIF-8@RAPA loses 15% more weight than ZIF-8, which is presumably due to the loaded RAPA, indirectly proving that RAPA is loaded in ZIF-8. In addition, the surface Zeta potentials of ZIF-8@RAPA and ZIF-8 are 26.8±0.8mV and 21.8±0.3mV, respectively, see Figure 3 -E. This result indicates that the loading of RAPA reduces the electromotive force of ZIF-8, which may be related to the presence of negatively charged groups such as hydroxyl groups in RAPA.
[0128] The present invention also investigated the effect of different addition amounts of RAPA methanol solution on drug loading rate, including final concentrations of 210 μg / mL, 420 μg / mL, 630 μg / mL, 730 μg / mL and 840 μg / mL. Figure 4 As shown, when the final concentration of RAPA methanol solution was 730 μg / mL, it had a better drug loading rate DLC%.
[0129] The above results indicate that RAPA is successfully loaded into the framework structure of ZIF-8 without changing the crystal structure of ZIF-8.
[0130] Example 3. In vitro drug release experiment of ZIF-8@RAPA
[0131] The delivery rate and time of the drug are closely related to the medium microenvironment, and play an important role in the efficacy of RAPA and the effective biological utilization. Therefore, this embodiment monitors the pH-responsive release of RAPA in ZIF-8@RAPA nanoparticles under PBS (pH5.5, pH6.5 and pH7.2). 20 mg of nanoparticles were dispersed in 5 mL of deionized water, placed in a blocked dialysis membrane, and then immersed in 40 mL of release medium. Since RAPA is a hydrophobic drug, 1% of polyoxyethylene ether was added to the release medium. Gently shake at 120 rpm in a constant temperature shaker at 37 ° C. At predetermined time intervals, take 1 mL of release buffer, measure with an ELISA instrument, and add the same amount of fresh buffer.
[0132] The results are as follows Figure 3 -F shows that PARA is released rapidly in an acidic environment (pH 5.5 and pH 6.5), but is released relatively slowly in a neutral environment. RAPA in the three groups is released rapidly in the first 24 hours, and the cumulative release rate gradually changes in the 24-96 hour stage, and basically reaches stability at 96 hours, and decreases with the increase of pH, which are 68.23%, 45.67%, and 35.96%, respectively. This result shows that ZIF-8 synthesized under the aforementioned optimized conditions is an effective drug delivery carrier that can achieve long-term sustained release, and has broad application prospects.
[0133] Example 4. Preparation of nanofiber membrane and oriented helical scaffold
[0134] (1) Preparation of nanofiber membranes with a “sandwich structure” (NFs / Z@R)
[0135] The outer layer used hexafluoroisopropanol as solvent, polycaprolactone with a concentration of 15% and type I collagen with a concentration of 18.75% as solutes, and the inner layer used dichloromethane:DMF=3:1 as solvent, PCL with a concentration of 15% and ZIF-8@RAPA with a concentration of 7% as solutes. The preparation parameters of the highly oriented spinning membrane (aNFs / Z@R(M)) were: shaft speed 4000rpm, voltage 25kV, injection speed 0.5mL / h, and receiving distance 18cm. The preparation parameters of the control group, the low-oriented spinning membrane (rNFs / Z@R(M)), were: shaft speed 500rpm, voltage 25kV, injection speed 0.5mL / h, and receiving distance 18cm.
[0136] (2) Preparation of oriented helical scaffolds (NFs / Z@R helical scaffolds)
[0137] The sandwich-structured nanofiber membrane was cut into 12 mm × 80 mm pieces, fixed on an improved mechanical stirring shaft, and the rotation speed was set to 30 rpm to prepare spiral scaffolds (aNFs / Z@R spiral scaffolds and rNFs / Z@R spiral scaffolds).
[0138] Example 5. Characterization of Nanofiber Membrane (NFs / Z@R)
[0139] The morphology and distribution of aNFs / Z@R and rNFs / Z@R were observed by SEM and TEM, and their mechanical properties, drug release behavior and cell compatibility were also tested. The experimental methods and results are as follows:
[0140] (1) Experimental methods
[0141] 1) SEM: The spun membrane was made into a sheet of 0.5 cm × 0.5 cm, fixed on the sample stage with conductive glue, and after gold spraying, the surface morphology and microstructure were observed and photographed using SEM under the conditions of accelerating voltage 5 kV and emission current 10 mA. The fiber orientation was observed and the diameter distribution was statistically analyzed.
[0142] 2) TEM: The electrospun fibers were spun onto a carbon film copper mesh. After drying, the morphology of the single fibers and the ZIF-8 therein were observed using TEM.
[0143] 3) Mechanical properties test: The film was cut into 40mm×10mm strips, and the test program was set to an effective distance of 20mm in the middle and a stretching rate of 10mm / min. The strips were stretched until they broke, and the displacement-force curve was recorded in real time. The mechanical properties of the fiber membrane were characterized by parameters such as breaking strength, breaking elongation, and Young's modulus.
[0144] 4) In vitro drug release: The release of RAPA from aNFs / Z@R nanofibers was monitored in PBS (pH 6.5 and pH 7.2). 20 mg of nanofibers were placed in 5 mL of deionized water and placed in a capped dialysis membrane, and then immersed in 40 mL of release medium. Since RAPA is a hydrophobic drug, 1% polyoxyethylene ether was added to the release medium. Gently shake at 120 rpm in a constant temperature shaker at 37°C. At predetermined time intervals, 1 mL of release buffer was taken, measured using an enzyme reader, and the same amount of fresh buffer was added.
[0145] 5) Cytocompatibility test: P3-P5 generation tendon stem cells (TSCs) were seeded on the scaffold material and cultured in a medium containing 10% fetal bovine serum and 1% penicillin / streptomycin (37°C, 5% CO2, 80% RH) for 24 hours. The cell activity was measured using the Live / Dead kit and the cell proliferation activity was measured using the EdU-555 kit. Further, the cells were fixed with paraformaldehyde and dehydrated in gradients, and the morphology of TSCs on the fibers was observed using SEM.
[0146] (2) Results and discussion
[0147] The morphology of aNFs / Z@R and rNFs / Z@R was observed by SEM, and the fiber orientation and fiber diameter were statistically analyzed. Figure 5 As shown, the orientation of aNFs / Z@R fibers is concentrated between -50°-50°, and the orientation of rNFs / Z@R fibers is concentrated between -100°-100°. The diameter of aNFs / Z@R fibers is concentrated between 0.2-0.4μm, and the diameter of rNFs / Z@R fibers is concentrated between 0.2-0.5μm. The distribution and morphology of ZIF-8@RAPA in a single fiber were observed by TEM, and it was found that ZIF-8@RAPA was wrapped in PCL fibers with clear edges and corners, and the morphology of ZIF-8 particles was not affected by spinning. For details, see Figure 6 .
[0148] The mechanical tensile test results are shown in Table 6. Figure 7 As shown in the figure, aNFs / Z@R has good mechanical properties, and its breaking strength and elastic modulus are better than those of the control group rNFs / Z@R, which is closely related to the orientation distribution of the fiber, indirectly proving that the oriented fiber preparation is successful. On the other hand, the breaking elongation of aNFs / Z@R is 33.4%±4.7%, which can meet the requirement of 10% elongation strain in tendon repair.
[0149] Table 6. Mechanical properties of aNFs / Z@R and rNFs / Z@R nanofiber membranes
[0150]
[0151] The long-term sustained release of RAPA is the prerequisite for it to exert its drug function, so the present invention tests the drug release behavior of aNFs / Z@R nanofiber membrane in vitro. Figure 8As shown in the figure, in both pH 6.5 and pH 7.2 environments, RAPA can be released slowly and continuously within a week, and the release rate of the former is higher than that of the latter, indicating that the release of RAPA can be promoted in the in vivo inflammatory environment (which can accelerate the formation of heterotopic ossification in tendons), inhibiting the formation of heterotopic ossification, and having pH sensitivity. SEM, Live / Dead staining and EdU staining results show that aNFs / Z@R nanofiber membrane has good cell compatibility, see for details Fig. 9 .
[0152] Example 6. Characterization of NFs / Z@R helical scaffold
[0153] The surface morphology of the NFs / Z@R spiral scaffold was observed by SEM, and the mechanical tensile properties and cell compatibility of the scaffold were tested. The experimental methods and results are as follows:
[0154] (1) Experimental methods
[0155] 1) SEM and mechanical properties testing, the methods are the same as Example 5.
[0156] 2) Cytocompatibility test: P3-P5 generation tendon stem cells (TSCs) were seeded on the scaffold material and cultured in a medium containing 10% fetal bovine serum and 1% penicillin / streptomycin (37°C, 5% CO2, 80% RH) for 24 hours. The cell viability and cell proliferation activity were determined using the Live / Dead kit and the EdU-555 kit, respectively. Further, the cells were fixed with paraformaldehyde and gradient dehydrated, and the morphology of TSCs on the fibers was observed using SEM.
[0157] (2) Results and analysis
[0158] The SEM test results are as follows Figure 10 to Figure 13 As shown in the figure, the number of spiral turns of the scaffold is evenly distributed, and the width of a single turn is about 500μm. Further magnification and observation show that the spiral processing has no effect on the fiber orientation in the local micro-region. The fibers in the aNFs / Z@R spiral scaffold show obvious orientation distribution, and there is a porous structure between the fibers, which is conducive to cell migration.
[0159] The mechanical tensile properties test results of the scaffold are shown in Table 7. The elastic modulus and fracture strength of aNFs / Z@R (helix) are higher than those of rNFs / Z@R (helix). At the same time, the addition of Z@R can improve the anisotropic mechanical properties of the scaffold.
[0160] Table 7. Mechanical properties of aNFs / Z@R(helical), aNFs(helical), and rNFs / Z@R(helical) scaffolds
[0161]
[0162]
[0163] Example 7. Tendon repair application
[0164] Heterotopic ossification is a common problem in the repair process of tendon tissue. Its occurrence will greatly reduce the tissue morphology, mechanical properties and subsequent functions of the tendon. Therefore, in order to visually observe the heterotopic ossification of the repaired Achilles tendon, this example uses micro-CT to analyze the repaired Achilles tendon samples of rats 6 weeks after surgery and performs three-dimensional reconstruction. At the same time, HE staining is used to evaluate the repair effect of the tendon. The specific experimental methods and results are as follows:
[0165] 1) Establishment of Achilles tendon injury model in SD rats and implantation of scaffolds
[0166] The surgical procedure for establishing the Achilles tendon defect model in SD rats is as follows: Fig.14 As shown. An appropriate amount of 1.5% sodium pentobarbital was injected into the rat's peritoneum for anesthesia, the skin of the right hind limb was cut, the fascia was separated to expose the Achilles tendon, and a complete defect of about 5 mm in length was made on the Achilles tendon 0.5 cm near the calcaneus. The two ends of the spiral stent (about 10 turns) were sutured with 6-0 sutures, and finally the skin tissue was sutured in sequence with 4-0 sutures.
[0167] 2) Characterization of tissue repair
[0168] Micro-CT imaging: Six weeks after surgery, rats were killed and Achilles tendon samples were collected. The samples were immersed in paraformaldehyde for 48 hours, and the solution was replaced with 75% alcohol for later use. After the liquid on the surface of the sample was dried with filter paper, it was placed on the test bench and the scanning parameters were set to: 10μm resolution, 55kV voltage, 200μA current.
[0169] HE staining: Six weeks after surgery, the rats were killed and the Achilles tendon samples were collected. After tissue fixation, gradient dehydration, paraffin embedding, sectioning, and dewaxing to water, hematoxylin and eosin (HE) staining was used, and the samples were observed under a microscope and photographed.
[0170] 3) Results
[0171] Representative micro-CT three-dimensional reconstruction results of the Achilles tendon in each group 6 weeks after surgery are shown in the figure. Fig.15 As shown in the figure, the degree of heterotopic ossification in the three groups is aNFs / Z@R (helix) < aNFs (helix) < rNFs / Z@R (helix), indicating that the fiber topology of the oriented helix and Z@R can inhibit the occurrence of heterotopic ossification to a certain extent, and the two play a synergistic role. The HE staining results are shown in the figure. Fig.16As shown in the figure, compared with the control group aNFs (spiral) and rNFs / Z@R (spiral), the ECM in the injured area of the aNFs / Z@R (spiral) tendon was denser, the cytoplasmic ratio was lower, the fiber arrangement tended to be orderly, and the histological morphology was well repaired. The results show that the aNFs / Z@R (spiral) scaffold can effectively repair the injured Achilles tendon and inhibit the occurrence of heterotopic ossification, and has broad application prospects.
Claims
1. A composition for preparing a directional helical stent, characterized in that: The composition includes a composition A for preparing an outer layer of a nanofiber membrane and a composition B for preparing an inner layer of a nanofiber membrane; The composition A comprises the following components: polycaprolactone and type I collagen at a concentration of 10% to 20%; in the composition A, the mass ratio of type I collagen to polycaprolactone is 15 to 25:100; The composition B comprises the following components: polycaprolactone with a concentration of 10% to 20% and a drug; in the composition B, the mass ratio of the drug to the polycaprolactone is 5 to 10:100; the drug is rapamycin with ZIF-8 as a carrier; The nanofiber membrane is made into a directional spiral stent by mechanical rotation.
2. The composition according to claim 1, characterized in that The composition A further comprises hexafluoroisopropanol; the composition B further comprises dichloromethane and DMF, and the volume ratio of the dichloromethane to DMF is 2 to 5:
1.
3. A method for preparing a directional helical stent using the composition according to any one of claims 1 to 2, characterized in that: The steps include: (1) ZIF-8 was used as a delivery vector for rapamycin to prepare ZIF-8@RAPA; (2) The outer layer uses hexafluoroisopropanol as solvent, polycaprolactone and type I collagen as solutes; the inner layer uses a mixed solution of dichloromethane and DMF as solvent, polycaprolactone and ZIF-8@RAPA obtained in step (1) as solutes; and a nanofiber membrane is prepared by electrospinning technology; (3) The nanofiber membrane obtained in step (2) is mechanically stirred to prepare a directional spiral stent.
4. The method according to claim 3, characterized in that Step (1) specifically includes the following steps: 1) dissolving zinc nitrate hexahydrate, and adding RAPA methanol solution to prepare a zinc-based solution; 2) using 2-methylimidazole as solute and methanol as solvent to prepare an imidazole solution; 3) adding the zinc-based solution obtained in step 1) to the imidazole solution obtained in step 2) to react and obtain ZIF-8@RAPA.
5. The method according to claim 4, characterized in that In step 3), the reaction conditions are as follows: stirring for 3 to 10 minutes, standing for 50 to 57 minutes, and the total reaction time is 60 minutes.
6. The method according to claim 4, characterized in that The final concentration of zinc ion is 0.015~0.025mol / L; 2-mIm - The final concentration is 0.10-0.2 mol / L; the concentration ratio of the zinc nitrate hexahydrate to the 2-methylimidazole is 1:7-10.
7. The method according to claim 3, characterized in that In step (2), the preparation parameters of electrospinning are: shaft speed 3500-4500 rpm, voltage 20-30 kV, injection speed 0.4-0.7 mL / h, and receiving distance 15-20 cm.
8. A directional spiral stent prepared by the method according to any one of claims 3 to 7.
9. A nanoparticle preparation for treating and repairing tendon damage and / or inhibiting heterotopic ossification, characterized in that: The nano preparation consists of a drug and a carrier; the drug is RAPA; the carrier is ZIF-8; and the nano preparation is prepared by a pharmaceutically acceptable method.
10. Use of the composition according to any one of claims 1 to 2, the directional helical stent according to claim 8 and / or the nanoformulation according to claim 9 in the preparation of a product for repairing tendon damage and / or inhibiting the occurrence of heterotopic ossification.
Citation Information
Patent Citations
Preparation method and application of zinc organic framework drug-loading system entrapping rapamycin
CN110693883A
Application of mammal rapamycin target protein (mTOR) blocker in preparation of medicines for treating calcified tendinopathy
CN111407727A
Gradient nano / microfiber scaffold as well as preparation method and application thereof
CN115068687A
Tendon repair material with antioxidant and antibacterial activity as well as preparation method and application of tendon repair material
CN118615489A
Double-layer multifunctional electrostatic spinning fibrous membrane wound dressing and preparation method thereof
CN118639393A